Find and explain the error in the student's work below.

Solve:
2c^2+c-6=0
2c²+ 4c-3c -6=0
2c(c + 2)- 3(c+2)=0
(c+2)(2c-3)=0
The student states that the answers are c + 2 and 2c - 3.

1 answer

The error in the student's work is that they mistakenly mixed up the signs in the final step. The correct final step should be:

(c + 2)(2c + 3) = 0

The correct answers are c + 2 and 2c + 3.
Similar Questions
  1. Find and explain the error in the​ student’s work below.​Solve: 2m² - 7m​ - 30​ = 0 2m² + 5m​ - 12m​ - 30​ = 0
    1. answers icon 1 answer
  2. Find and explain the error in the​ student’s work/answer below.​Solve: ​ 2c² + c​ – 6​ = 0 ​ 2c² + 4c​ –
    1. answers icon 1 answer
  3. Find and explain the error in the​ student’s work/answers below.​Solve: ​ m² + m​ – 6​ = 0 ​ m² – 2m​ +
    1. answers icon 3 answers
  4. Find and explain the error in the​ student’s work below.Solve​ 2x² - 5x​ -12 = 0 using the Quadratic Formula.
    1. answers icon 1 answer
more similar questions